An essay on comparison as a method in social sciences - Nikolinakos, Marios (The Greek Review of Social Research, 1977)
I would summarize the argument of this paper in the following points: a) Every scientific research is of political relevance in the Aristotelian as well as in a politoeconomie sense, or it is useless. b) Time and space as the two definitional elements of comparison give the historical dimension of the phenomena. Difference or similarity of phenomena is thus reduced to difference of similarity of conditions at two or more points in time and in space, which is a question of the reproducibility of historical conditions. c) Comparison as a method implies the comparability of two things and aims at showing equality between them or proving their inequality. d) Comparability is a function of the concept used to define a phenomenon and in this sense relative by definition. e) There are two distinct aspects in the process of comparison: the one referring to the identification of a phenomenon—which means defining its properties—the other to the degree of similarity (or equality) of two or more phenomena at two or more different points in time and/or in space. f) Comparison in a narrow sense as a method in social sciences aims at measuring the degree of similarity between two or more objects in time and/or in space. The comparative method in a narrow sense is thus the techniques and procedures of research in the service of the above aim. g) Every technique of measuring phenomena in the process of comparing needs to be justified in its scope, in its implications, finally in relation to the object of measurement. h) The operation of identification of phenomena in the comparative method is common to all social sciences. Comparison as an operation of measuring the degree of similarity between two or more phenomena is not identical in all social sciences. The techniques of measurement for each discipline differ according to the phenomena to be observed and compared as well as according to the general scope of comparing. i) The comparative method in a narrow sense has been proposed and developed in the postwar period primarily as a method of comparing phenomena across cultures and nations. j) The main three plausible reasons for crosscultural comparative research are: 1) the concern with the economic development of developing countries in the postwar period (historical reason); 2) the testing of hypotheses and theories beyond national boundaries aiming at revealing «laws» (comparison as a substitute for experiment) (methodological reason); 3) practical policy aims (political reason). k) The concept of «nation» is to be preferred to the concept of «culture» in discussing comparison as a method of social research; crosscultur- al is taken, therefore, to mean crossnational. l) Diffusion leads to a homogenisation of phenomena across cultures and nations which has been increasing in the postwar period although this has not yet led to an elimination of national differences. m) It is possible to observe tendencies across cultures and nations, furthermore to detect developments, but it is questionable whether it is possible to compare them in a strict sense for three main reasons referring to the problem of identification, the reliability of data and measurement itself. n) Crosscultural comparison aiming at testing theories or general hypotheses must find in at least two systems the causes leading to the same effect in both of them (explanation part of a theory), furthermore to fix the conditions that are sufficient and necessary for a reproduction of the same phenomenon at a later point in time or at a different point in space (prediction part of a theory). Such a task has been so far unsuccessful. o) Policy implications arising out of a study in other nations are only of conditional relevance for some other. Even assuming the similarity of conditions it is uncertain if the development of a phenomenon will follow the same track in a new country that it had followed in one or more other countries previously. p) Also the comparative method is either useless or is of political relevance (point a). On the grounds of conclusion under o, the comparative method must be declared either as «useless» or political in terms of politics, and not in terms of policy implementation.